2021
DOI: 10.1088/1755-1315/819/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between mangrove ecosystem with shoreline change in Indramayu coast

Abstract: Mangrove ecosystem in Indramayu coast has function to preserve coastal area from abrasion and sedimentation as destructive hazard, because mangrove has ability to reduce impact of abrasion and sedimentation in coastal ecosystem. Before 2018, Indramayu regency had shore line coast until 115.5 km, but abrasion caused the degradation of shore line in Indramayu coast until more than 20%. This research aimed to analysis correlation between mangrove ecosystem with shoreline change in Indramayu Coast. The research me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…And the highest mangrove seedling density occurred in the utilization zone, reaching an average of 70,000 trees/ha. The potential data on mangrove density showed that the mangrove ecosystem in Muara Kali Ijo is regenerating (Hilmi et al 2015;Nur and Hilmi 2021). Mangrove density, domination, and regeneration of mangrove species have a positive impact on the potentials of plankton (Andriyani et al 2020;Hilmi et al 2020), other micro and macro-organisms (Su et al 2012;Yin et al 2018), land animal habitats, other organisms, and birds (Putra et al 2019;Wolswijk et al 2020).…”
Section: Mangrove Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…And the highest mangrove seedling density occurred in the utilization zone, reaching an average of 70,000 trees/ha. The potential data on mangrove density showed that the mangrove ecosystem in Muara Kali Ijo is regenerating (Hilmi et al 2015;Nur and Hilmi 2021). Mangrove density, domination, and regeneration of mangrove species have a positive impact on the potentials of plankton (Andriyani et al 2020;Hilmi et al 2020), other micro and macro-organisms (Su et al 2012;Yin et al 2018), land animal habitats, other organisms, and birds (Putra et al 2019;Wolswijk et al 2020).…”
Section: Mangrove Densitymentioning
confidence: 99%
“…The EEA in Muara Kali Ijo aims to support the conservation of the mangrove ecosystem as an essential ecosystem in Pantai Ayah, Kebumen, because the mangrove ecosystem has a specific affinity (Hilmi et al 2021e), specific environment (Hilmi et al 2021a(Hilmi et al , 2022bXiong et al 2018), specific habitat (Hilmi 2018;Hilmi et al 2021d;Purnama et al 2022), and specific ecosystem (Cochard 2017;Hilmi et al 2015;Lapolo et al 2018). In addition, the mangrove ecosystem in Muara Kali Ijo also has specific functions to reduce and protect tidal flooding (Hilmi et al 2022a;Marois and Mitsch 2017) and permanent water inundation (Bomer et al 2020), decreasing of coastal disasters (Cooray et al 2021;Nur and Hilmi 2021), decreasing of heavy-metal pollution (Chen et al 2021;Hilmi et al 2017b;Syakti et al 2013;Xin et al 2014;Zhang et al 2019), support carbon conservation (Hilmi 2017a), and support feeding, nursery dan spawning activity (Jones et al 2015;Lapolo et al 2018;Nurhayati et al 2021;Reis et al 2021). Besides, the mangrove ecosystem in Muara Kali Ijo is also used as a tourism area and Crocodylus porosus preservation (Tim Penyusun EEA Kali Ijo Kebumen 2020).…”
Section: Introductionmentioning
confidence: 99%
“…High and permanent water inundation in direct planting systems caused high mortality, stunting growth, lower biodiversity and trigger of species domination. Nur and Hilmi (2021) and Hilmi et al (2021a) explained that tidal waves and water inundation primarily affect mangrove growth. Water inundation is caused by water dynamics occurring due to river discharge and tidal waves (Hilmi et al 2017a;Suhendra et al 2018).…”
Section: Physical and Chemical Parametersmentioning
confidence: 99%
“…The mangrove ecosystem in the north coast of Jakarta, Indonesia is an estuarine mangrove ecosystem type located on the northern coast of the Java Island facing toward Java Sea (Hilmi et al 2017a;Onrizal et al 2005), which is influenced by freshwater supply from the Citarum River, Bekasi River, and Ciliwung River (Hilmi et al 2017a;Kusumahadi et al 2020). This mangrove ecosystem has irreplaceable ecosystem services, for example, as the buffer to mitigate the risk of coastal disasters, including tsunamis (Giri et al 2015;Hilmi 2018;Nur and Hilmi 2021;Suhendra et al 2018), tidal flooding (Krauss and Allen 2003;Ysebaert et al 2016) and land subsidence (Bomer et al 2020;van Wesenbeeck et al 2015), and serve as the habitat of aquatic organisms (Abubakar et al 2018;Masni et al 2016), as well as improving other ecosystem services (Duncan et al 2016) by reducing wave energy and sediment stabilization (Ndirangu et al 2017). In addition, the mangrove ecosystem in the northern coast of Jakarta has a specific affinity (Hilmi et al 2021b), specific adaptation to reduce the impact of water inundation and flooding, pollution, salinity, and soil texture (Andriyani et al 2020;Barreto et al 2016;Hilmi et al 2017a;Hilmi et al 2021a;Tam et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation